Hydropower Development in Nepal: Lessons from Past Models - Pun, Santa Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2008)
In the last six decades since the 1951 overthrow of Rana regime, hydropower development in Nepal was implemented under various models depending on the donors. The 1950s and ‘60s were the era of bilateralism to be subsumed by multilateralism of the 1970s and ‘80s only to be trodden over by liberalization and privatization of the 1990s and 2000. If one were to scrutinize these bilateral, multilateral and liberalized models in the hydropower sector closely, certain interesting patterns emerge. Nepal could well learn lessons from them. Hydro Nepal: Journal of Water, Energy and Environment Issue No. 2, (2008) pp. 5-8